2021
DOI: 10.1017/s0142716421000291
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation preferences in contexts with three antecedents: examining the role of prominence in German pronouns

Abstract: This paper focuses on the relational notion of prominence, in which entities of equal type are ranked according to certain prominence-lending features. In German two demonstrative forms, “der” and “dieser”, can function like personal pronouns in English. It has been proposed that processing “der” involves computing a prominence hierarchy of the prior referents, and excluding the referent with the highest prominence rank. The demonstrative “dieser” has not been extensively tested. In the current study, personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…Dieser, Patil et al (2023) argue, is not sensitive to perspective-taking, but also avoids the most prominent discourse referent, which is then the discourse topic. Patterson and Schumacher (2021) found no significant difference between the use of der and dieser in forced-choice and acceptability judgment tasks of ambiguous contexts with three antecedents, but both showed a certain preference for the last mentioned antecedent, supporting the claim of Zifonun et al (1997) for dieser. Finally, Patil et al (2020) found register differences between der and dieser, such that dieser tends toward more formal, and der toward more informal, language.…”
Section: Anaphorically Used Demonstrative Pronounssupporting
confidence: 70%
See 3 more Smart Citations
“…Dieser, Patil et al (2023) argue, is not sensitive to perspective-taking, but also avoids the most prominent discourse referent, which is then the discourse topic. Patterson and Schumacher (2021) found no significant difference between the use of der and dieser in forced-choice and acceptability judgment tasks of ambiguous contexts with three antecedents, but both showed a certain preference for the last mentioned antecedent, supporting the claim of Zifonun et al (1997) for dieser. Finally, Patil et al (2020) found register differences between der and dieser, such that dieser tends toward more formal, and der toward more informal, language.…”
Section: Anaphorically Used Demonstrative Pronounssupporting
confidence: 70%
“…This is actually in line with previous studies that have described a potential subject or first-position preference for personal pronouns (cf. Kaiser and Trueswell, 2008;Kaiser, 2011;Fuchs and Schumacher, 2020;Patterson and Schumacher, 2021). We reserve some doubt about these results since the same effect did not emerge in our second pair of experiments (2a and 2b; see below).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In (1) the factors of subjecthood and agenthood align such that the firefighter is the subject and agent of the sentence, whereas the boy is the object and patient of the sentence. However, when subjecthood and agenthood don't align, German pronouns show a mixed effect of subjecthood and agenthood (Schumacher et al, 2016;Patterson & Schumacher, 2021).…”
Section: Personal Vs Demonstrative Pronouns In Germanmentioning
confidence: 99%